A hope unprepared to accept things as they are”: Engaging John de Gruchy’s challenges for “Theology at the edge” - Boesak, Allan (Nederduitse Gereformeerde Teologiese Tydskrif, 2015)
This article argues, in conversation with the work of John de Gruchy, for the continuation of the struggle for the integrity of the prophetic witness of the church in the world. Prophetic theology is, as all true prophetic theology always is, indeed a theology “on the edge” – always on the edge of challenge and risk, of confrontation with the powers and principalities of our present age. The article also challenges the waves of Christian neo-fundamentalism washing over Africa and much of the global South with its toxic neo-colonialist package deal of scriptural selectivity, violent homophobia, patriarchal power, and anti-justice agenda. Prophetic theology should be much better prepared to take on the challenges posed by it. Prophetic theology, furthermore, is not rooted in the hope of acceptance by those who rule the world, but grounded in the hope that is unprepared to accept the world as it is and as the powerful have made it; a hope in the reign of God that will overcome the reign of terror that rules our world.